Influence of amino acids on the growth of Bacteroides melaninogenicus. - Miles, D O (1976)
Addition of individual amino acids to a Trypticase-yeast extract-hemin medium affected growth rates and final yields of an asaccharolytic strain and a saccharolytic strain of Bacteroides melaninogenicus. L-Aspartate or L-asparagine produced maximal growth enhancement for both strains. L-[14C]aspartate was fermented by resting cells of the asaccharolytic strain. L-Cysteine or L-serine also enhanced growth for the saccharolytic strain. However, growth of the saccharolytic strain was inhibited by L-lysine, L-glutamate, L-glutamine, L-isoleucine, L-leucine, and L-proline; growth of the asaccharolytic strain was inhibited by DL-valine and L-serine. Both strains were inhibited by L-histidine, DL-methionine, L-tryptophan, L-arginine, and glycine.